2020
DOI: 10.3389/fphar.2019.01648
|View full text |Cite
|
Sign up to set email alerts
|

Improved Computational Identification of Drug Response Using Optical Measurements of Human Stem Cell Derived Cardiomyocytes in Microphysiological Systems

Abstract: Cardiomyocytes derived from human induced pluripotent stem cells (hiPSC-CMs) hold great potential for drug screening applications. However, their usefulness is limited by the relative immaturity of the cells' electrophysiological properties as compared to native cardiomyocytes in the adult human heart. In this work, we extend and improve on methodology to address this limitation, building on previously introduced computational procedures which predict drug effects for adult cells based on changes in optical me… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
83
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 45 publications
(83 citation statements)
references
References 70 publications
(117 reference statements)
0
83
0
Order By: Relevance
“…In the present study, our principal aim was to generalize the methods we have developed previously 12,13 for extrapolating drug effects obtained using hiPSC-CMs to healthy, mature human ventricular myocytes. Importantly, we found that the an equivalent approach can be used to translate measured pharmacological effects on the action potential in animal models to those in healthy adult human myocytes by employing the same models for the same currents in different cell types.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In the present study, our principal aim was to generalize the methods we have developed previously 12,13 for extrapolating drug effects obtained using hiPSC-CMs to healthy, mature human ventricular myocytes. Importantly, we found that the an equivalent approach can be used to translate measured pharmacological effects on the action potential in animal models to those in healthy adult human myocytes by employing the same models for the same currents in different cell types.…”
Section: Discussionmentioning
confidence: 99%
“…11,51,52 . In our computations, we use the Base model developed in 13 , as it systematically uses the same model for the identical ion channel in two different species. Note that in 13 the results of the Base model is compared to the results of the Paci model (for immature cells) and to the Grandi et al model and the ORd model (adult human cells).…”
Section: Supplementary Informationmentioning
confidence: 99%
See 3 more Smart Citations